2020
DOI: 10.2166/nh.2020.036
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the conditional behavior of rainfall deficiency and groundwater level deficiency signatures by using copula functions

Abstract: The complex hydrological events such as storm, flood and drought are often characterized by a number of correlated random variables. Copulas can model the dependence structure independently of the marginal distribution functions and provide multivariate distributions with different margins and the dependence structure. In this study, the conditional behavior of two signatures was investigated by analyzing the joint signatures of groundwater level deficiency and rainfall deficiency in Naqadeh sub-basin in Lake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Various Copula families have been introduced so far. Application of Archimedean ( Tahroudi et al., 2020 ; Xu et al., 2019 ) and other Copula families are common in hydrological problems ( Dehghani et al., 2019 ; Li et al., 2019 ; Zhang and Singh, 2007 ). Hence, this study used some of these families (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Various Copula families have been introduced so far. Application of Archimedean ( Tahroudi et al., 2020 ; Xu et al., 2019 ) and other Copula families are common in hydrological problems ( Dehghani et al., 2019 ; Li et al., 2019 ; Zhang and Singh, 2007 ). Hence, this study used some of these families (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…where X 11 À X 12 ð Þand X 21 À X 22 ð Þare independent and evenly distributed copies of X 1 , X 2 ð Þ (Ramezani et al, 2019;Tahroudi et al, 2020b).…”
Section: Kendall's Tau Correlationmentioning
confidence: 99%
“…In the traditional methods of flood frequency analysis, one of the assumptions for analyzing flood frequency is that hydrologic series are independent and follow the same distribution (Maidment 1993). However, human activities and climate change have influenced all rivers around the world ( Jain & Lall 2000;Zhang et al 2008;Vogel et al 2011;Li et al 2013;Hu et al 2015;Machado et al 2015;Tahroudi et al 2019Tahroudi et al , 2020bWei et al 2020;Sharifi et al 2021) as well as non-stationary properties in hydrological phenomena (Jain & Lall 2000). These features affect the base assumptions of flood frequency analysis and the associated reliability (Khozeymehnezhad & Nazeri-Tahroudi 2020).…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…The proposed approach was adopted to investigate the dynamics of hydrological and meteorological droughts in the Zarinehroud basin, Lake Urmia, Iran. Tahroudi et al (2020b) used the conditional behavior of two signatures to analyzing the signatures of rainfall deficiency and groundwater-level deficiency in the Naqadeh sub-basin, Lake Urmia Basin, Iran, based on copulas. They showed that the presented conditional density function was an alternative method to the conditional return period.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%